2020
DOI: 10.3390/ijerph17062146
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and Non-Cancer Risk Concerns from Metals in Electronic Cigarette Liquids and Aerosols

Abstract: We evaluated metal concentrations in e-liquids and e-aerosols from eight studies and estimated the range of corresponding cancer and non-cancer risks. Chromium and nickel were the leading contributors to cancer risk, with minor contributions from cadmium, lead, and arsenic. The increased cancer risks, assuming exposure to 2 mL/day, ranged from 5.7 to 30,000 additional cancers in a million e-cigarette users. The average cancer risk was 3 in 1000. Cancer risks in the mid to upper end of these ranges exceed accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…Except for Au, these metals are consistent with those reported in previous nicotine device liquids and heated aerosol measurements [ 12 16 ]. These metals represent a potential chronic health risk when inhaled, though estimated risks have exceeded health limits mostly under high temperature or high usage scenarios [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Except for Au, these metals are consistent with those reported in previous nicotine device liquids and heated aerosol measurements [ 12 16 ]. These metals represent a potential chronic health risk when inhaled, though estimated risks have exceeded health limits mostly under high temperature or high usage scenarios [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The metals in EC products have not yet been directly linked to these illnesses, and such linkage may be challenging to demonstrate given the high variability in metal transfer to EC aerosols from different products and the variations in user topography [ 43 ], which also affects metal concentrations in aerosols [ 44 ]. A recent risk assessment study based on published concentrations of metals in EC products concluded that nickel and chromium are high enough in EC liquids and aerosol to present a cancer risk and that nickel, chromium, and manganese may also present non-cancer health risks [ 45 ]. In addition, human urine samples from EC users had higher concentrations of zinc than those from nonsmokers, and zinc concentration was positively correlated with increased DNA oxidation, suggesting a potential increased risk for disease in the EC user group [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-powered and open-system devices are likely to have higher metal content in aerosol than closed systems ( 130), but none of the metal content is likely to generate significant adverse health effects (131). FOWLES et al (132) concluded in a review that metals in vapour could constitute a health risk to EC users but that high product standards can minimize exposure and reduced health risks associated with metals in EC aerosol.…”
Section: Impurities and Leachingmentioning
confidence: 99%